Antityrosinase and antioxidant activities of guanidine compounds and effect of guanylthiourea on melanogenesis. (October 2019) - Wang, Yu-Xia; Su, Wei-Chao; Wang, Qin; Lin, Yu-Feng; Zhou, Yuan; Lin, Long-Fang; Ren, Su; Li, Yan-Ting; Chen, Qing-Xi; Shi, Yan
Graphical abstract: Highlights: Four guanidine compounds (GCs) exhibited significant antityrosinase activities. Dynamic and quantitative observation on the interaction of tyrosinase and GCs were studied. The models and theories of structural functional relationships of GCs were developed. Guanylthiourea exhibited a significantly inhibitory effect on melanin synthesis. Abstract: In this study, the antityrosinase and antioxidant activities of four guanidine compounds (GCs), including guanylthiourea (GT), guanidine thiocyanate (GTC), phenylguanidine (PG), and phenethyldiguanide (PTDG), were investigated. The results showed that the GCs reduced the monophenolase and diphenolase activities of tyrosinase. The IC50 values of GT, GTC, PG, and PTDG were 0.27, 3.53, 6.68, and 5.18 mM for monophenolase and 0.23, 3.24, 3.97 and 2.50 mM for diphenolase, respectively. The inhibition of diphenolase activity was reversible for the four GCs. The inhibition types of GT and PTDG were competitive, while those of GTC and PG were mixed. FRAP, ABTS, DPPH, and DNA damage protection assays revealed that only GT possessed significant antioxidant activity. Furthermore, GT was found to decrease the melanin content and expression of TYR, MITF and DCT in both B16F10 cells and zebrafish. Overall, our results indicated that GT can inhibit tyrosinase activity in vitro, which suggests that these GCs are potential candidates for novel small-molecule tyrosinase inhibitors and that GT could have broader application prospects.